Determination of transient interfacial tension in a microfluidic device using a Laplace sensor. (14th December 2019) - Lan, Wenjie; Wang, Zhihui; Wang, Miao; Liu, Dan; Guo, Xuqiang; Sun, Qiang; Li, Xingxun; Li, Shaowei
Highlights: A Laplace sensor was developed for determination of transient interfacial tension. The method can accurately measure the interfacial tension as low as 0.17 mPa·s. TIFT in two-phase dispersion coupling mass transfer processes was determined. The two-phase flow rates and composition will significantly influence TIFT. Abstract: In two-phase dispersion processes coupled with interphase mass transfer, the interfacial tension varies with the mass transfer and significantly affects the dispersion. Determination of the transient interfacial tension (TIFT) in such processes could facilitate better understanding and optimization of the existing processes. In this study, a microfluidic device in which a Laplace sensor was used as a pressure probe was developed to determine the TIFT. The developed Laplace sensor was shown to allow accurate measurement of the local pressure in a micro-device, and to be superior to a commercial pressure sensor. The new method can be used to precisely determine the interfacial tension when the dispersion rate was not higher than 1.5 Hz, and to have a measurement range not narrower than 0.17–58.53 mPa·s. The TIFTs of several systems were then determined, and a mathematical model was established to predict the results. The main factors governing the TIFT were analyzed based on both the experimental and theoretical results.